Exchanging data between SAS® and Microsoft Excel : tips and techniques to transfer and manage data more efficiently - Benjamin, William E. (SAS Institute, 2015)
Master simple-to-complex techniques for transporting and managing data between SAS and Excel William Benjamin's Exchanging Data between SAS and Microsoft Excel: Tips and Techniques to Transfer and Manage Data More Efficiently describes many of the options and methods that enable a SAS programmer to transport data between SAS and Excel. The book includes examples that all levels of SAS and Excel users can apply to their everyday programming tasks. Because the book makes no assumptions about the skill levels of either SAS or Excel users, it has a wide-ranging application, providing detailed instructions about how to apply the techniques shown. It contains sections that gather instructional and syntactical information together that are otherwise widely dispersed, and it provides detailed examples about how to apply the software to everyday applications. These examples enable novice users and power developers alike the chance to expand their capabilities and enhance their skillsets. By moving from simple-to-complex applications and examples, the layout of the book allows it to be used as both a training and a reference tool. Excel users and SAS programmers are presented with tools that will assist in the integration of SAS and Excel processes in order to automate reporting and programming interfaces. This enables programming staff to request their own reports or processes and, in turn, support a much larger community.